2015
DOI: 10.1002/2014jf003318
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic constraints on fault throw rates and linkage times: Examples from the Northern Gulf of Evia, Greece

Abstract: We evaluate how the growth and interaction of active normal faults in the Sperchios Basin and Northern Gulf of Evia, Greece, are recorded by the landscape. We demonstrate that patterns in footwall relief along the faults reflect fault segmentation, and we show that in this study area, fault throw is 2 to 3 times the maximum footwall relief. Rivers crossing the faults typically have two knickpoints, which are unrelated to lithology. However, their heights, measured from the active fault trace, vary systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 72 publications
(311 reference statements)
8
75
0
Order By: Relevance
“…Researchers have exploited these evolutionary characteristics of normal fault systems to assess the geomorphic response to step changes in the rate of local rock uplift (Boulton and Whittaker, 2009;Whittaker and Boulton, 2012;Whittaker and Walker, 2015;Kent et al, 2016). Following these previous studies and based on the observation that the Ptolemy and South-Central Crete faults linked in the geologically recent past (< 1 Ma), we infer that along the Tsoutsouros section of the fault uplift rates increased rapidly following linkage.…”
Section: Relationships Between Fault Growth Linkage and Footwall Upsupporting
confidence: 88%
See 1 more Smart Citation
“…Researchers have exploited these evolutionary characteristics of normal fault systems to assess the geomorphic response to step changes in the rate of local rock uplift (Boulton and Whittaker, 2009;Whittaker and Boulton, 2012;Whittaker and Walker, 2015;Kent et al, 2016). Following these previous studies and based on the observation that the Ptolemy and South-Central Crete faults linked in the geologically recent past (< 1 Ma), we infer that along the Tsoutsouros section of the fault uplift rates increased rapidly following linkage.…”
Section: Relationships Between Fault Growth Linkage and Footwall Upsupporting
confidence: 88%
“…This history is consistent with the conceptual model presented in Fig. 2 and supports the findings of numerous other studies that show that river profiles are sensitive recorders of relative uplift histories (Snyder et al, 2000;Whipple, 2001, 2012;Wobus et al, 2006;Whittaker et al, 2008;Boulton and Whittaker, 2009;Pritchard et al, 2009;Whittaker and Boulton, 2012;Perron and Royden, 2013;Royden and Perron, 2013;Goren et al, 2014;Whittaker and Walker, 2015).…”
Section: Along-strike Patternsmentioning
confidence: 99%
“…The upper set of knickpoints are attributed to the initiation of faulting and the resulting growth of topography. The lower set of knickpoints are interpreted as the result of subsequent increase (3-5×) in throw rate due to fault linkage (Whittaker and Walker, 2015). The elevations of each group of knickpoints both scale with footwall relief,…”
Section: An Example Of a Tectonically Active Site: Gulf Of Evia Greecesupporting
confidence: 86%
“…We explore a series of basins draining across faults in the Sperchios Basin, Gulf of Evia, Greece (Figure 11), predominantly cut into 10 clastic sediments (Eliet and Gawthorpe, 1995). Previous work (Whittaker and Walker, 2015) has demonstrated that catchment morphology reflects interaction with these faults. The rivers are typically characterised by convex longitudinal profiles that commonly have two knickpoints.…”
Section: An Example Of a Tectonically Active Site: Gulf Of Evia Greecementioning
confidence: 75%
See 1 more Smart Citation